Developing Speaking Skill of Grade VIII Students through English Video - Ismawati, Hera; M. Said, Mawardin; Wahyudin, Wahyudin; Hasyim, Zarkiani (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This research aims to find out the effectiveness of English videos in developing students' speaking skills at the VIII grade of SMP Negeri 12 Palu. This research employed a quantitative approach with a quasi-experimental design. The research population consisted of 6 classes of SMP Negeri 12 Palu students. The samples were class VIII A as the experimental class and VIII B as the control class. This research utilized oral test as the research instrument to assess students' speaking skills. A pretest was given, followed by different treatments for both classes. The experimental class used English videos as learning media, while the control class did not. After giving the posttest, the researcher analyzed the results statistically to determine the significant difference between both classes. The results show that the mean score of the experimental class significantly developed from 36.30 to 56.54, while the mean score of the control class developed from 38.23 to 42.64. The hypothesis testing results also show that the t-counted value (3.188) was higher than the t-table value (1.688) at a significance level of 0.05, thus confirming that the use of English videos is effective in developing students' speaking skills of grade VIII of SMP Negeri 12 Palu.